Fenomena Pekerja Anak (Kasus Pedagang Asongan Anak di Kawasan Ekonomi Khusus Mandalika, Lombok Tengah) - Minawati Anggraini; Siti Nurjannah; Oryza Pneumatica Inderasari (Prodi Sosiologi Universitas Mataram, 2020)
The phenomenon of child labor food street sellers is a complex problem which currently exists in both. This research is aimed to investigate phenomenon of a child food street in the Mandalika Economic Region and meaning of children’s rights for child food street sellers. The research method used is a phenomenology qualitative approach. The main resource of this research is children working as street food sellers. The research results show that being a food street seller is affected by past actions in order to achieve goals. They work almost every day after school time. As street food sellers, most of them define their rights as a child as being fulfilled but some are not. The conclusion that can be drawn from this research is (1) children who become food street sellers have two sets of motives. The first relate to their friends, family economic conditions, up bringing patterns, looseness of school rules, and self-willingness. The secondary motives relate to playing to strengthen social relations, to assist their family’s economic circumstances, to bring happiness to their family, to become free from homework, to be independent, and to improve their English. (2) The meaning of children’s rights for child food street sellers is the right to play, to receive education, protection, a name, nationality, food, health, recreation, equality, and a role in development. The researcher gives some suggestions such as this study can be a reference for policy-making in the mentoring program.